Bordetella bronchiseptica Colonization Limits Efficacy, but Not Immunogenicity, of Live-Attenuated Influenza Virus Vaccine and Enhances Pathogenesis After Influenza Challenge - Hughes, Holly R.; Brockmeier, Susan L.; Loving, Crystal L. (Frontiers in Immunology, 2018)
Intranasally administered live-attenuated influenza virus (LAIV) vaccines provide significant protection against heterologous influenza A virus (IAV) challenge. However, LAIV administration can modify the bacterial microbiota in the upper respiratory tract, including alterations in species that cause pneumonia. We sought to evaluate the effect of Bordetella bronchiseptica colonization on LAIV immunogenicity and efficacy in swine, and the impact of LAIV and IAV challenge on B. bronchiseptica colonization and disease. LAIV immunogenicity was not significantly impacted by B. bronchiseptica colonization, but protective efficacy against heterologous IAV challenge in the upper respiratory tract was impaired. Titers of IAV in the nose and trachea of pigs that received LAIV were significantly reduced when compared to non-vaccinated, challenged controls, regardless of B. bronchiseptica infection. Pneumonia scores were higher in pigs colonized with B. bronchiseptica and challenged with IAV, but this was regardless of LAIV vaccination status. While LAIV vaccination provided significant protection against heterologous IAV challenge, the protection was not sterilizing and IAV replicated in the respiratory tract of all LAIV vaccinated pig. The interaction between IAV, B. bronchiseptica, and host led to development of acute-type B. bronchiseptica lesions in the lung. Thus, the data presented do not negate the efficacy of LAIV vaccination, but instead indicate that controlling B. bronchiseptica colonization in swine could limit the negative interaction between IAV and Bordetella on swine health.